Dionysius Bar Ṣalībī's Treatise Against the Jews : Edited and Translated with Notes and Commentary - Ebied, Rifaat, (Texts and Studies in Eastern Christianity ;, 2019)
"Dionysius Bar Ṣalībī's Treatise against the Jews offers rare and illuminating insight into Christian-Jewish-Muslim relations during the Crusader era, not from the perspective of western Crusaders, but from the frequently neglected viewpoint of the Oriental Orthodox tradition. Bar Ṣalībī, a distinguished hierarch of the Syrian Orthodox Church, lived in a turbulent time of heightened tensions in the Levant. The Treatise against the Jews, which forms part of the corpus of Syriac polemical works, investigates the prejudices of Christians and Jews towards each other during the 12 century AD.This edition and translation is based on all the available manuscripts of the text, accompanied by extensive introductions, notes and commentary as well as studies of its place in the field of Syriac Patristic polemics"--